HUBUNGAN FAKTOR SOSIODEMOGRAFI, KLINIS, DAN PENGAWAS MINUM OBAT TERHADAP KEBERHASILAN PENGOBATAN TUBERKULOSIS PARU DI PUSKESMAS RAPAK MAHANG TENGGARONG - Fadilla, Shella; Moerad, Emil Bachtiar; Tandirogang, Nataniel (Jurnal Medika : Karya Ilmiah Kesehatan, 2023)
Tuberculosis (TB) is a contagious and infectious disease caused by Mycobacterium tuberculosis which mainly affects the lungs. Due to its high morbidity and mortality rate, it is necessary to control and manage it with tuberculosis treatment program. The indicator for evaluating this program focusses on the treatment success rate. One way to reach tuberculosis treatment success rate is analyzing factors concerning the result treatment. This study aims to investigate the correlation among socio-demographic factors (i.e. age, sex, distance of residence, and education), clinical factors (i.e. diagnosis type and Diabetes Melitus (DM) status), and drug consumption supervisor towards treatment success for pulmonary tuberculosis. The design of this study was anaytical observational with cross-sectional approach. Applying total sampling technique, the data were collected from Tuberculosis Information System, TB form, and medical records at TBDOTS (Directly Observed Treatment Short-course) Unit of Rapak Mahang Public Health Centre in Tenggarong from 2020 to 2022. There were 94 samples fulfilling inclusion and exclusion criteria. The data were analyzed using Fisher’s Exact test. The results of statistical analysis including age, sex, distance of residence, education, diagnosis type, DM status, and drug consumption supervisor were shown by p value of 0,454; 0,548; 1,000; 1,000; 0,573; 0,410; and 1,000 consecutively. Therefore, it can be concluded that each of these following factors: age, sex, distance of residence, education, diagnosis type, DM status, and drug supervisor is not significantly correlated with the treatment success for pulmonary TB.